2022
DOI: 10.1523/eneuro.0442-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hypothalamic MCH Neuron Development in a 3D Differentiation System of Mouse Embryonic Stem Cells

Abstract: Hypothalamic melanin-concentrating hormone (MCH) neurons are important regulators of multiple physiological processes, such as sleep, feeding, and memory. Despite the increasing interest in their neuronal functions, the molecular mechanism underlying MCH neuron development remains poorly understood. We report that a three-dimensional culture of mouse embryonic stem cells (mESCs) can generate hypothalamic-like tissues containing MCH-positive neurons, which reproduce morphologic maturation, neuronal connectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
(151 reference statements)
0
2
1
Order By: Relevance
“…We did not observe any Nkx2.1- or Nkx2.2-positive cells in the absence of SAG, although it has been shown that such ventral hypothalamic cells appear regardless of the absence of SAG (Kodani et al, 2022; Wataya et al, 2008). This is presumably due to the differences of the cell lines used in each study.…”
Section: Methodscontrasting
confidence: 73%
See 1 more Smart Citation
“…We did not observe any Nkx2.1- or Nkx2.2-positive cells in the absence of SAG, although it has been shown that such ventral hypothalamic cells appear regardless of the absence of SAG (Kodani et al, 2022; Wataya et al, 2008). This is presumably due to the differences of the cell lines used in each study.…”
Section: Methodscontrasting
confidence: 73%
“…For differentiation, three thousand ES cells were seeded onto a 96-well non-absorbable plate (Greiner, Cell-Repellent, #650970) and cultured in growth factor-free chemically defined medium We did not observe any Nkx2.1-or Nkx2.2-positive cells in the absence of SAG, although it has been shown that such ventral hypothalamic cells appear regardless of the absence of SAG (Kodani et al, 2022;Wataya et al, 2008). This is presumably due to the differences of the cell lines used in each study.…”
Section: Maintenance and Differentiation Of Mouse Es Cellsmentioning
confidence: 85%
“…We further identified two subpopulations of MCH LH/ZI neurons and delineated their discrete functional relevance: motor behaviors (MCH LH/ZI→SNpc ) and non-motor behaviors (MCH LH→HPC ). This finding is noteworthy because it has not been studied whether the separate subpopulations of MCH LH/ZI neurons have distinct projections involving differential functions in the system level, despite recent highlights on the diversity of several hypothalamic neurons (43)(44)(45). Our findings strongly suggest that these two distinct circuits from MCH LH/ZI neurons are the cellular and circuit-level neuroanatomical basis of the multi-function of acupuncture in PD (Fig.…”
Section: Discussionmentioning
confidence: 72%